Derek Parfit: concern of no one as myself - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The article discusses the personality and legacy of Derek Parfit. He entered the history of modern metaphysics and moral philosophy as a proponent of radical NeoLockean view on the issues of personal identity. Denying our basic metaphysical and moral intuitions (identity for the person and moral responsibility), the so-called «Oxford Buddhist» was a tireless preacher of hyper-rational altruism. His original ideas and admirable arguments outlined only in few works were and remain at the center of philosophical discussions